Визначення типу дизеля при ремоторизації тепловозів ЧМЕ3 - Адам, Юліан Ярославович; Adam, Yulian Yaroslavovych (Національний університет "Львівська політехніка", 2024)
Більше третини робіт на залізничному транспорті виконуються маневровими локомотивами. На залізницях України основним маневровим тепловозом являється тепловоз серії ЧМЕ3. Парк цих локомотивів в Україні перевищує тисячі одиниць. Дані тепловози почали випускатись з 1963 року. Тому на даний момент вони виробили свій термін служби. Але по розрахункам проектних організацій рами тепловозів мають ще деякий запас міцності і їх можна експлуатувати до 50 років. В той же час дизеля К6S310DR вже виробили свій ресурс та морально застаріли. При цьому техніко-економічні показники їх не відповідають сучасному рівню і вони вже не випускаються виробником. Закупка нових маневрових тепловозів, особливо в теперішніх умовах, визиває багато складностей, починаючи від ціни і закінчуючи термінами виконання. Тому модернізація тепловозів раціональними енергетичними установками представляє великий інтерес. У бакалаврській кваліфікаційній роботі вирішується актуальна задача вибору дизельної енергетичної установки для ремоторизації тепловозів ЧМЕ3. Об’єкт дослідження – локомотивні енергетичні установки для маневрових тепловозів. Предмет дослідження – методи розрахунку параметрів дизеля та його систем, масляної та охолодження дизеля. Мета дослідження – визначити раціональний тип дизеля для ремоторизації маневрового тепловозу ЧМЕ-3 з врахуванням його технічного стану. За результатами кваліфікаційної роботи виконано такі задачі досліджень: - проведено аналіз різних видів модернізації тепловозів ЧМЕ3 різними виробниками та фірмами; - побудовано моделі розрахунку дизеля, системи охолодження та масляної системи; 5 - отримані техніко-економічні показники дизелів САТ та K6S310DR, а також перевірені штатні системи тепловоза ЧМЕ3 охолодження та масляна система на предмет відводу тепла від дизеля САТ. Аналіз різних видів модернізації тепловозів ЧМЕ3 показав доцільність їх проведення з врахуванням стану тепловозів. Основним питанням при модернізації тепловозу є питання вибору енергетичної установки. Найдешевшим способом модернізації тепловозу є його ремоторизація. З усіх розглянутих видів модернізації тепловозу ЧМЕ3 для України є доцільним використання дизелів САТ 3508В потужністю 970 кВт. На основі існуючих методів були побудовані в маткаді моделі розрахунку основних техніко-економічних показників дизеля, системи його охолодження та масляної системи. Результати розрахунків техніко-економічних характеристик дизеля Cat3508B показав, що вони по питомій витраті палива до 15% мають кращі показники в порівнянні з дизелем K6S310DR. Штатна система охолодження позволяє відводити лишнє тепло від дизеля САТ, але її низький ккд в порівнянні з запропонованою системою катерпілер показує доцільність встановлення нової масляної системи та системи охолодження.

More than a third of the work on railway transport is performed by shunting locomotives. On the railways of Ukraine, the main shunting diesel locomotive is the ChME3 series diesel locomotive. The fleet of these locomotives in Ukraine exceeds 8 thousands of units. These diesel locomotives began to be produced in 1963. Therefore, at the moment they have exhausted their service life. But according to the calculations of design organizations, the frames of diesel locomotives still have some margin of safety and can be operated for up to 50 years. At the same time, the K6S310DR diesel engines have already exhausted their resource and are morally obsolete. At the same time, their technical and economic indicators do not correspond to the modern level and they are no longer produced by the manufacturer. The purchase of new shunting diesel locomotives, especially in the current conditions, causes many difficulties, starting from the price and ending with the deadlines. Therefore, the modernization of diesel locomotives with rational power plants is of great interest. The bachelor's qualification work solves the urgent problem of choosing a diesel power plant for remotorization of ChME3 diesel locomotives. Object of the research – locomotive power plants for shunting diesel locomotives.. Subject of the research – methods for calculating the parameters of a diesel engine and its systems, oil and diesel cooling. Purpose of the research – to determine the rational type of diesel engine for remotorization of the ChME-3 shunting locomotive, taking into account its technical condition. According to the results of the qualification work, the following research tasks were completed: - an analysis of various types of modernization of ChME3 diesel locomotives by different manufacturers and companies was carried out; - models for calculating the diesel engine, cooling system and oil system were built; - technical and economic indicators of the CAT and K6S310DR diesel engines were obtained, as well as the standard systems of the ChME3 diesel locomotive, cooling and oil system, were checked for heat removal from the CAT diesel engine. Analysis of various types of modernization of ChME3 diesel locomotives showed the feasibility of carrying them out taking into account the condition of the diesel 9 locomotives. The main issue when modernizing a diesel locomotive is the issue of choosing a power plant. The cheapest way to modernize a diesel locomotive is its remotorization. Of all the considered types of modernization of the ChME3 diesel locomotive, the use of CAT 3508V diesel engines with a capacity of 970 kW is appropriate for Ukraine. Based on existing methods, models for calculating the main technical and economic indicators of the diesel engine, its cooling system and oil system were built in Matkad. The results of calculations of the technical and economic characteristics of the Cat3508B diesel engine showed that they have better performance in terms of specific fuel consumption by up to 15% compared to the K6S310DR diesel engine. The standard cooling system allows you to remove excess heat from the CAT diesel engine, but its low efficiency compared to the proposed Caterpillar system shows the feasibility of installing a new oil system and cooling system.
Determining the type of diesel engine when remotorizing diesel locomotives ChME3
Keywords: 6.273.00.02; тепловоз ЧМЕ 3; ремоторизація; дизель; система охолодження; масляна система; diesel locomotive ChME 3; remotorization; diesel; cooling system; oil system